STRATEGI PEMASARAN BANK SYARIAH MANDIRI DALAM MENINGKATKAN PENJUALAN PRODUK PENSIUN - Iskandar Ritonga; Eka Purwati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
This study aims to (1) Determine the marketing strategy of Bank Syariah Mandiri in increasing sales of pension products, (2) The strengths and weaknesses of the marketing strategy of Bank Syariah Mandiri in increasing product sales. The result of this research is that the marketing strategy is the marketing activities carried out by the Bank’s management in order to achieve the marketing target. This marketing Strategy is structured based on what should be done, who does, and when to do it. The marketing strategy used by Bank Syariah Mandiri in increasing sales of pension products is by using an approach and promotion strategy. This approach to customers can enhance Bank Syariah Mandiri’s long-term growth and maximum customer satisfaction. After carrying out the approach process, the next stage is the promotion strategy. Promotion is an activity that aims to convey information about pension products to customers, so that the pension product is known and can encourage customers to use it. Promotion is also very useful for providing information about the advantages or disadvantages of these retirement products.